Pediococcus spp.-fermented chicken meat for dogs - Eunchae Lee (Journal of Animal Science and Technology, 2020)
An experiment was conducted to evaluate Pediococcus spp.-fermented chicken meat as a snack for dogs. The fermented or non-fermented snacks used in this study were prepared through the following process; meat mixtures containing 52.8% MDCM, 35.2% chicken breast meat (CBM) and 9.7% corn starch were inoculated with or without Pediococcus spp., incubated at 37°C for 24 h and then sterilized at 121°C for 20 min. During the 24-h fermentation, the pH of fermented chicken snack dropped rapidly with concomitant increase in number of lactic acid bacteria. The nutritional composition was not altered by fermentation. In vitro pepsin nitrogen digestibility was higher (p < 0.05) in the fermented snack compared with the non-fermented snack. Upon storage at room temperature for 14 days, bacteria grew slowly in fermented vs. non-fermented snack samples. In a palatability trial, dogs preferred non-fermented over fermented snack food. In 12-d-long feeding trial, fecal ammonia content was lowered, but fecal lactic acid content was increased in dogs fed the fermented vs. non-fermented snack food. Our study shows that the fermented MDCM-based snack exhibited good preservability upon storage, and improved in vitro nitrogen digestibility and fecal characteristics in dogs.